Integrating Triply‐ and Singly‐Bent Highly Flexible Crystal Optical Waveguides for Organic Photonic Circuit with a Long‐Pass‐Filter Effect. Issue 2 (10th December 2021) - Annadhasan, Mari; Pradeep, Vuppu Vinay; Kumar, Avulu Vinod; Ravi, Jada; Chandrasekar, Rajadurai
Abstract : Fabrication of organic photonic integrated circuits (OPICs) greatly relies on crystalline materials with high mechanical flexibility and fluorescence (FL). Realizing an efficient OPIC with multiple photonic functions suitable for practical applications depends on creating complex circuit architectures. The mechanical and optical functions of crystals are susceptible to subtle differences in the molecular packing and, more importantly, the type of intermolecular interactions. Herein, an organic crystal ( E )‐1‐(4‐(iodo)phenyl)iminomethyl‐2‐hydroxyl‐naphthalene (IPIN) exhibiting high flexibility under mechanical stress, bright green FL, and selective self‐absorbance of the blue part of its broadband FL signal is reported. IPIN microcrystal transduces its FL effectively even in its bent geometry. The significant crystal‐surface adhesion energy facilitates the micromechanical fabrication of a triply‐bent waveguide using a mechano(crystal)photonic approach, which is later integrated with a singly‐bent waveguide to create a unique OPIC. This futuristic OPIC delivers excitation position‐dependent and direction‐specific long‐pass‐filtered narrowband optical signals with different split ratios. Abstract : Fluorescent organic crystal ( E )‐1‐(4‐(iodo)phenyl)iminomethyl‐2‐hydroxyl‐naphthalene (IPIN) exhibits exceptional mechanical flexibility and selective self‐absorption of the blue part of its emission. IPIN crystal forms a triply‐bent waveguide during micromechanical fabrication. Integration of a triply‐bent waveguide with a singly‐bent waveguide creates a unique organic photonic integrated circuit (OPIC) geometry. This innovative OPIC carries excitation position‐dependent and direction‐specific long‐pass‐filtered narrowband optical signals with different split ratios.